Comparing stalking, intimate partner violence and sexual assault: the impact on attitudes towards men and intimacy in female victims - Goodchild, Christie (2019)
Despite research concerning the psychological consequences of women’s experiences of stalking, sexual assault and intimate partner violence (IPV), little is known about the impact they have on attitudes towards men and intimacy. Data were collected from 196 women who had and had not experienced stalking, sexual assault and/or IPV by a male perpetrator, and analysed with reference to the hostility subscale of the Ambivalence Towards Men Inventory and the Intimacy Attitudes Scale. Data were also collected concerning the number of examples of stalking, sexual assault and IPV that participants had experienced from a list of examples. Findings suggest that, for hostility towards men, experiencing all three offences leads to more hostile attitudes than experiencing none of them and stalking alone. For intimacy, findings suggest that experiencing all three offences and a combination of sexual assault and IPV are associated with a lower capability for intimacy in comparison to experiencing none of the offences and sexual assault alone. Number of experiences of each offence was positively and significantly correlated with hostility, and negatively and significantly correlated with intimacy. This suggests that more experiences of stalking, sexual assault and IPV are associated with more hostile attitudes towards men and lower capabilities for intimacy. Implications and limitations of the study are discussed, and recommendations for further research are outlined.